The Effect of Sport Activities on Self-Confidence Levels of 13-14 Year-Olds - Salih Tutku Yaylacı; Çisem Ünlü (Journal of Educational Issues, 2024)
This study is conducted to determine the effect of the sport activities on the self-confidence levels of 13-14 year-olds. Self-confidence formation starts especially at ages of 13-14 and affects the success of the individuals. Therefore, whether sport activities have any effects on self-confidence and whether the demographic characteristics affect self-confidence are analyzed in our study. Total of 272 individuals, 159 individuals participating in sport activities and 113 individuals not participating in sport activities at Ilkadım, Carsamba and Bafra Youth Centers providing services under the scope of the sport activities by the Samsun Youth and Sports Provincial Directorate in the season of 2018-2019 have participated voluntarily in this study. In this research, survey method among the methods used in applied research is preferred. As the data collection tool, a survey form consisting of two sections is used. In the first section the ‘Personal Information Form’ prepared by the researcher is used. In the personal information form, demographic information as father’s employment status, mother’s employment status, mother and father’s marital status, number of siblings and familial income status are included. In the second section, the ‘Self-confidence scale’ developed by Akın (2007) is used. Acquired data is tested at 95% confidence level with the aid of SPSS program and the significance level is determined as 0.05. In the light of the date in the study, before the statistical analysis was begun, normality assumption and homogeneity tests are applied, as the result of the Kolmogorov-Smirnov and Levene tests conducted it is determined that the data has normal distribution (p > 0.05). As the data shows normal distribution, it is decided to conduct parametric analysis. In comparison of the groups, independent sample t-test and one way ANOVA analyses are used. According to the acquired data and the analyses conducted, as the result of comparison of the Internal and External Self-confidence scores of the individuals participating in the sport activities according to the father’s employment status, mother’s employment status, mother and father’s marital status, number of siblings and familial income status, it is concluded that there is no significant differences. Whereas in the gender variable, while there is no significant difference in the Internal Self-confidence sub dimension, in the External Self-confidence sub dimension it is found out that the males have significantly higher scores compared to the females. Also it is seen that the self-confidence levels of individuals participating in sport activities are statistically higher than the ones who do not participate in the sport activities (p < 0.05).